Framing the Forgotten: Beauty, Innocence, and Religiosity in the Representation of Indonesian Comfort Women - Az-Zahra, Nur Aisyiah (Universitas Gadjah Mada, 2025)
This research examines the documentary *Because We Were Beautiful* (2010), which focuses on the testimonies of Indonesian *juugun ianfu* (military comfort women) who experienced sexual violence during the Japanese occupation of the Netherlands East Indies (present-day Indonesia) from 1942 to 1945. Framed through a feminist lens, this study utilizes Cockburn's concept of